2021
DOI: 10.1364/ao.443498
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a 2 × 2 MIMO-UWOC system with large spot against air bubbles

Abstract: In order to reduce turbulence-induced scintillation and deal with alignment problems, a 2 × 2 multiple-input multiple-output (MIMO) underwater wireless optical communication (UWOC) system is proposed and experimentally demonstrated. With help of the large divergence angle of light beams and large field of view (FOV) of the detectors, the effect of high-density air bubbles is greatly eliminated. Simulation and experimental results confirm that, in most intensity-modulation/dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, problems such as turbulenceinduced flicker and difficulties in aligning the communication link can be reduced. In 2022 [62] , Zhejiang University demonstrated that the 2×2MIMO-UWOC system can mitigate the impact of underwater bubbles and link misalignment on communications.…”
Section: The Uwoc System Technical Problems and Solution Pathsmentioning
confidence: 99%
“…In addition, problems such as turbulenceinduced flicker and difficulties in aligning the communication link can be reduced. In 2022 [62] , Zhejiang University demonstrated that the 2×2MIMO-UWOC system can mitigate the impact of underwater bubbles and link misalignment on communications.…”
Section: The Uwoc System Technical Problems and Solution Pathsmentioning
confidence: 99%
“…These implementations are actually semiphysical simulations with idealized processing of receiving signals rather than real-time and deployable MIMO-UWOC systems. Additionally, these systems are bulky, heavy, and expensive [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%